PENGARUH PERMAINAN TEKA-TEKI SILANG TERHADAP KEMAMPUAN PENGENALAN HURUF ANAK DI TK BUNDO KANDUANG SIBARAMBANG KABUPATEN SOLOK - Nurmai Yunis; Serli Marlina (STKIP Subang, 2026)
The ability to identify alphabetic characters is a fundamental skill that must be developed during early childhood, as it serves as the foundation for early reading competence. Based on observational findings conducted at Bundo Kanduang Sibarambang Kindergarten located in Solok Regency, it is still apparent that children experience challenges in recognizing letter symbols, articulating letter names, and distinguishing between nearly identical letter shapes. The purpose of this study was to investigate the impact of crossword puzzle games on children's letter recognition abilities. This study employed a quantitative methodology using direct experimental techniques. The research subjects were in group B of Bundo Kanduang Sibarambang Kindergarten, Solok Regency. Data collection methods were applied through observation, documentation, and child development assessment instruments. The research findings indicate that engagement with crossword puzzles significantly improves children's letter recognition abilities. This game also contributes to increased concentration, memory, and motivation for learning. Consequently, crossword puzzle games can be considered an effective pedagogical medium for improving early childhood letter recognition skills.